Accidents in the food-manufacturing small and medium sized Malaysian industries - Hussin, Zaliha; Jusoff, Kamaruzaman; Ju, Soon Yew; Kong, Lai Kuan (Canadian Center of Science and Education, 2008)
This research tried to find out the types and causes of accidents that happen in food-manufacturing factories in small and medium-sized industries (SMIs) in Kedah and the actions taken by the employers following the occurrence of the accidents. Results showed that majority of the respondents had encountered slight injuries. The majority of the accidents were caused by human factors, and employers seldom took serious actions against those involved in workplace accidents. Small cut was identified as the commonest type of accident that occurred in the SMIs for the past two years. Findings also indicated that many of the employers were less interested in giving out incentives when their employees complied with all the safety rules and regulations while punishments were less serious for those who do not complied with safety rules and regulations.